SOFSEM 2016 : theory and practice of computer science : 42nd International Conference on Current Trends in Theory and Practice of Computer Science, Harrachov, Czech Republic, January 23-28, 2016, Proceedings /: theory and practice of computer science : 42nd International Conference on Current Trends in Theory and Practice of Computer Science, Harrachov, Czech Republic, January 23-28, 2016, Proceedings. (2016) - Unknown
No abstract available